Three-dimensional superresolution fluorescence microscopy maps the variable molecular architecture of the nuclear pore complex - Jimenez Sabinina, Vilma; Hossain, M. Julius; Hériché, Jean-Karim; Hoess, Philipp; Nijmeijer, Bianca; Mosalaganti, Shyamal Narayan; Kueblbeck, Moritz; Callegari, Andrea; Szymborska-Mell, Anna Boźena; Beck, Martin; Ries, Jonas; Ellenberg, Jan (Molecular biology of the cell, 2021)
Nuclear pore complexes (NPCs) are large macromolecular machines that mediate the traffic between the nucleus and the cytoplasm. In vertebrates, each NPC consists of ∼1000 proteins, termed nucleoporins, and has a mass of more than 100 MDa. While a pseudo-atomic static model of the central scaffold of the NPC has recently been assembled by integrating data from isolated proteins and complexes, many structural components still remain elusive due to the enormous size and flexibility of the NPC. Here, we explored the power of three-dimensional (3D) superresolution microscopy combined with computational classification and averaging to explore the 3D structure of the NPC in single human cells. We show that this approach can build the first integrated 3D structural map containing both central as well as peripheral NPC subunits with molecular specificity and nanoscale resolution. Our unbiased classification of more than 10,000 individual NPCs indicates that the nuclear ring and the nuclear basket can adopt different conformations. Our approach opens up the exciting possibility to relate different structural states of the NPC to function in situ.
Gesehen am 25.10.2021